2017
DOI: 10.1111/tri.13040
|View full text |Cite
|
Sign up to set email alerts
|

Lower quality of life in young men after pediatric kidney transplantation when compared to healthy controls and survivors of childhood leukemia-a cross-sectional study

Abstract: Data about health-related quality of life (HRQOL) in adult recipients after pediatric kidney transplantation (KTx) are scarce. In this nationwide questionnaire-based study, HRQOL and social status in young adult men having undergone KTx during childhood (n = 29) were studied and compared to age- and gender-matched healthy controls (n = 56) and survivors of childhood acute lymphoblastic leukemia (n = 52) comprising controls with another chronic disease of childhood. Altogether 41% of the KTx recipients, 50% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(45 citation statements)
references
References 26 publications
0
45
0
Order By: Relevance
“…By contrast, our study is in agreement with the more recent study by Brownbridge and Fielding, who found no significant difference between dialysis and post‐transplant patients. Recent data from Finland suggest that the problem only worsens upon transition to adulthood . The quality of life among former pediatric renal transplant recipients in early adulthood is worse than that of pediatric cancer survivors, even if there is good graft function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, our study is in agreement with the more recent study by Brownbridge and Fielding, who found no significant difference between dialysis and post‐transplant patients. Recent data from Finland suggest that the problem only worsens upon transition to adulthood . The quality of life among former pediatric renal transplant recipients in early adulthood is worse than that of pediatric cancer survivors, even if there is good graft function.…”
Section: Discussionmentioning
confidence: 99%
“…30 In an older study, Reynolds et al 30 TA B L E 2 Socioeconomical characteristics adulthood. 32,33 The quality of life among former pediatric renal transplant recipients in early adulthood is worse than that of pediatric cancer survivors, even if there is good graft function.…”
Section: Ing Depression Scores Among Pediatric Ckd Patients In Centralmentioning
confidence: 99%
“…A major limitation of the present study is the relatively small number of study patients. Secondly, we focused only on male patients and excluded those with significant co‐morbidities since this study is part of a larger follow‐up study evaluating fertility and quality of life in young men after pediatric KTx . Thirdly, we used previously recruited control groups and, thus, we could not perfectly match the cohorts by their age and relevant medical history.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, we focused only on male patients and excluded those with significant co-morbidities since this study is part of a larger follow-up study evaluating fertility and quality of life in young men after pediatric KTx. 2,32 Thirdly, we used previously recruited control groups and, thus, we could not perfectly match the cohorts by their age and relevant medical history. NBL survivors were significantly younger at the time of diagnosis than the KTx recipients at initiation of dialysis, and they had a longer history with severe chronic disease than the KTx patients.…”
Section: Discussionmentioning
confidence: 99%
“…Data on the health-related quality of life (HRQOL) are scant. In this context, we are delighted to see the study by Kira End en et al in this edition of Transplant International, entitled 'Lower quality of life in young men after pediatric kidney transplantation when compared to healthy controls and survivors of childhood leukemia -a cross-sectional study' [10]. Their study included 29 former paediatric renal transplant recipients, 52 survivors of childhood-onset acute lymphoblastic leukaemia (ALL) and 56 age and gendermatched controls, during the period of 1983-2011.…”
mentioning
confidence: 99%